Influência da rugosidade no comportamento ao desgaste dos aços inoxidáveis nitretados para uso em biomateriais - Roxadelli, Francielli (2019)
Stainless steels can be used as biomaterials for the preparation of orthopedic and dental implants. The integration of the metal with the human body occurs on the surface of the material which is also the region of greatest stress, therefore the most susceptible to degradation (TALHA et. al., 2013; PARK e LAKES, 2007). Surface treatments of plasma nitriding are usually employed to improve the wear and corrosion resistance of stainless steels, in addition to having a bactericidal effect (CASTELETTI et al; 2010). It is known that implants with rough surfaces favor osseointegration (BRANDÃO, 2010). In order to study the influence of the roughness on the wear resistance of plasma nitrided 304 and 316L stainless steels for biomedical application, surfaces of 304 and 316L stainless steels, having a #400 roughness and polished in diamond solution of up to 9 micrometres were prepared. Subsequently nitrided to plasma with a temperature of 400ºC for 4 hours. The analyzes were done with optical microscopy, scanning electron microscopy, X-ray diffraction, Vickers hardness measurements with 490.3mN and 980.7mN loads, profilometry, scratch tests with load ranging from 2 to 8N and wear tests. Plasma nitriding promoted greater wear resistance and the use of the hot wall reactor was effective to maintain the surface roughness of the samples. However, the samples of 316L steel showed a non-uniform nitrided layer, presenting lower results than the 304 steel. The sanded samples obtained a better performance when compared to the polished samples, presenting a critical load about 30% higher.